PENGOLAHAN UBI KAYU MENJADI MAKANAN TELA - TELA DALAM MENINGKATKAN EKONOMI MASYARAKAT DIMASA PANDEMI DI KELURAHAN LUMUT KECAMATAN LUMUT KABUPATEN TAPANULI TENGAH - Azriadi Tanjung; Fauziah Nur Simamora; Hesty Amelia Gultom; Nurwahidah Simamora (COVIT (Community Service of Health), 2022)
The purpose of implementing this community partnership program (PKM) service is (1) understanding PKM in the Lumut Village community, (2) understanding in Processing Cassava into Tela - Tela Food, (3) understanding business management management. The method of implementing cassava processing activities into Tela - Tela food includes five stages, namely: (1) Introduction stage, (2) Socialization and audience stage, (3) Training and Processing Stage, (4) making product, (5) . Final Evaluation Stage. PKM community service partners are the Lumut Village Community, Lumut District, Central Tapanuli Regency. This program is carried out as an effort to add insight to the community and PKK mothers in processing Cassava. This activity is also useful as an innovation in making products, namely Tela - Tela Food from Cassava and improving the economy of local residents. This program is expected to run well and increase public awareness. The result of this mentoring program is the expected output of scientific publications in proceedings and national journals with ISSN. Keywords: Cassava Processing, Into Food Tela - Tela